Pangenalan penggunaan Data Science untuk melakukan Analisis Sentimen di SMAN 1 Tanjung Bintang - Nirwana Hendrastuty; m. ghufroni an'ars; Damayanti Damayanti; Fitrah Amalia; Samuel Hutagalung; Chris Mario; M. Tova (Universitas Teknokrat Indonesia, 2023)
Currently, various groups and ages, almost all Indonesian people own and use social media as a means of obtaining and conveying information to the public. This is an opportunity for data scientists to carry out sentiment analysis on topics or opinions conveyed by the public. Sentiment analysis is used to find out whether the opinion or post has a positive, negative or neutral meaning. Unfortunately there are still many students who do not know this. From these problems the servant team provides a solution to conduct data science training, especially in sentiment analysis of public figures. The target of this activity is students of class XI and XII from SMAN 1 Tanjung Bintang. The implementation of community service for the assisted school scheme consists of three stages, namely, preparation, implementation and evaluation. The preparatory stage is carried out by carrying out a survey first to find out the problems experienced by partners and carry out an analysis to find solutions to these problems. From the results of the distribution of questionnaires in the training, it was found that an increase in understanding of data science, especially sentiment analysis, was an average of 1.8, previously students got an average pre-test of 5.1 and a post-test of 6.9.